An upgraded groundwater quality evaluation based on Hasse diagram technique & game theory. (July 2022) - Ding, Fei; Chen, Liangyao; Sun, Chiyin; Zhang, Wenjie; Yue, Hongjie; Na, Shuhan
Graphical abstract: Highlights: Determine weights between subjective and objective weights based on game theory. A new evaluation model of groundwater quality based on Game theory-HDT is proposed. Propose a new dimensionless method to reduce computation and upgrade Game theory-HDT. Abstract: To upgrade the groundwater quality evaluation model based on the Hasse diagram technique (HDT), this paper established a new evaluation model based on game theory and HDT. This new model, Upgraded-HDT, has been upgraded in three aspects: selection of the weighting method, combination of weights and simplification of the model calculation steps. The groundwater quality data of nine sample sites in Ganjingzi district of Dalian city in 2013 were used as a case to validate the model. The evaluation results of Upgraded-HDT showed that the groundwater quality of all sites was class III or better, apart from site 5, which was deeply affected by seawater intrusion and pollutant seepage. In addition, the evaluation results of the nemerow pollution index (NPI), fuzzy comprehensive evaluation (FCE), AHP-HDT, Entropy-HDT, Game theory-HDT and Upgraded-HDT were compared and analyzed. The results of AHP-HDT, although verifying the importance of expert experience in evaluating the model, were not sufficiently accurate at sites 4 and 6, while the results of Entropy-HDT at sites 7, 8 and 9 were overly optimistic and did not reflect the real situation of groundwater quality. Hence, the use of a single weighting method could not accurately evaluate water quality. The results of Game theory-HDT were the most accurate and the same as Entropy-HDT at site 4 and AHP-HDT at sites 6, 7 and 8. This showed that in game theory regarding the optimal combination of weights, the advantages of the two complement each other because both take into account the subjective initiative of people and avoid the one-sidedness of a single weighting method. Thus, the use of game theory was necessary. The results of Upgraded-HDT and Game theory-HDT agreed perfectly, which not only ensured the accuracy of the evaluation results but also reduced the computation of the HDT model. This proved that the dimensionless method proposed in this paper was feasible. The results of this study can provide a scientific basis for the protection and utilization of local groundwater resources and serve as a reference for water quality evaluation studies in other areas.